Metaheuristics and Optimization in Civil Engineering - Yang, Xin-She.; Bekdaş, Gebrail; Nigdeli, Sinan Melih; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This timely book deals with a current topic, i.e. the applications of metaheuristic algorithms, with a primary focus on optimization problems in civil engineering. The first chapter offers a concise overview of different kinds of metaheuristic algorithms, explaining their advantages in solving complex engineering problems that cannot be effectively tackled by traditional methods, and citing the most important works for further reading. The remaining chapters report on advanced studies on the applications of certain metaheuristic algorithms to specific engineering problems. Genetic algorithm, bat algorithm, cuckoo search, harmony search and simulated annealing are just some of the methods presented and discussed step by step in real-application contexts, in which they are often used in combination with each other. Thanks to its synthetic yet meticulous and practice-oriented approach, the book is a perfect guide for graduate students, researchers and professionals willing to applying metaheuristic algorithms in civil engineering and other related engineering fields, such as mechanical, transport and geotechnical engineering. It is also a valuable aid for both lectures and advanced engineering students.
Keywords: Civil engineering; Computational intelligence; Mechanics, Applied; Operations research; Civil Engineering; Computational Intelligence; Engineering Mechanics; Operations Research and Decision Theory